Caught between two Allee effects: Trade-off between reproduction and predation risk - Pavlová, Viola; Berec, Lude˘k; Boukal, David S. (Journal of theoretical biology, 2010)
Reproductive activities are often associated with conspicuous morphology or behaviour that could be exploited by predators. Individuals can therefore face a trade-off between reproduction and predation risk. Here we use simple models to explore population-dynamical consequences of such a trade-off for populations subject to a mate-finding Allee effect and an Allee effect due to predation. We present our results in the light of populations that belong to endangered species or pests and study their viability and resilience. We distinguish several qualitative scenarios characterized by the shape and strength of the trade-off and, in particular, identify conditions for which the populations survive or go extinct. Reproduction can be so costly that the population always goes extinct. In other cases, the population goes extinct only over a certain range of low, intermediate or high levels of reproductive activities. Moreover, we show that predator removal (e.g. in an attempt to save an endangered prey species) has the least effect on populations with low cost of reproduction in terms of predation and, conversely, predator addition (e.g. to eradicate a pest) is most effective for populations with high predation cost of reproduction. Our results indicate that a detailed knowledge of the trade-off can be crucial in applications: for some trade-off shapes, only intermediate levels of reproductive activities might guarantee population survival, while they can lead to extinction for others. We therefore suggest that the fate of populations subject to the two antagonistic Allee effects should be evaluated on a case-by-case basis. Although the literature offers no quantitative data on possible trade-off shapes in any taxa, indirect evidence suggests that the trade-off and both Allee effects can occur simultaneously, e.g. in the golden egg bug Phyllomorpha laciniata.